2021
DOI: 10.7150/thno.47723
|View full text |Cite
|
Sign up to set email alerts
|

A thermosensitive, reactive oxygen species-responsive, MR409-encapsulated hydrogel ameliorates disc degeneration in rats by inhibiting the secretory autophagy pathway

Abstract: Lumbar disc degeneration is a common cause of chronic low back pain and an important contributor to various degenerative lumbar spinal disorders. However, currently there is currently no effective therapeutic strategy for treating disc degeneration. The pro-inflammatory cytokine interleukin-1β (IL-1β) mediates disc degeneration by inducing apoptotic death of nucleus pulposus (NP) cells and degradation of the NP extracellular matrix. Here, we confirmed that extracellular secretion of IL-1β via secretory autopha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 76 publications
0
33
0
Order By: Relevance
“…173 ROS-responsive capsule hydrogels loaded with MR409 effectively inhibited secretory autophagy and acupuncture-induced exacerbation of IVDD in rats. 174 Notably, glucose oxidase and ferrous glycinate triggered cascade enzyme polymerization reactions leading to fast curing of chondroitin sulfate methacrylate (CSMA) and acrylamide hydrogels. 175 This facilitates rapid healing of bone defects and provides a tunable strength bionic strategy for IVD tissue engineering of bioimplant materials and 3D printed scaffolds.…”
Section: Stimulus-responsive Composite Hydrogelsmentioning
confidence: 99%
“…173 ROS-responsive capsule hydrogels loaded with MR409 effectively inhibited secretory autophagy and acupuncture-induced exacerbation of IVDD in rats. 174 Notably, glucose oxidase and ferrous glycinate triggered cascade enzyme polymerization reactions leading to fast curing of chondroitin sulfate methacrylate (CSMA) and acrylamide hydrogels. 175 This facilitates rapid healing of bone defects and provides a tunable strength bionic strategy for IVD tissue engineering of bioimplant materials and 3D printed scaffolds.…”
Section: Stimulus-responsive Composite Hydrogelsmentioning
confidence: 99%
“…Prior studies have revealed the marked impairment of autophagy in degenerative tissues ( Zhong et al, 2022 ). Enhanced autophagy flux ameliorates oxidative stress, alleviates the progression of degenerative alterations, and enhances the cellular regenerative activity ( Yao et al, 2018 ; Zheng et al, 2021 ). Increasing number of studies have indicated that m6A-mediated autophagy was involved in the regulation of IVDD and other degenerative diseases ( Yao et al, 2018 ).…”
Section: Interaction Between M6a and Autophagymentioning
confidence: 99%
“…23−25 It is demonstrated that autophagy would capture and degrade dysfunctional organelles to sustain metabolism and homeostasis. 24,26,27 Nevertheless, there is a complex relationship between autophagy and tumor treatment. use of block copolymer/CP hybrid composites has been a promising approach to enhance the stability of CP particles.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there remains an obstacle underlying that cancer could develop protective mechanisms to skip cell apoptosis in PDT. It is demonstrated that autophagy would capture and degrade dysfunctional organelles to sustain metabolism and homeostasis. ,, Nevertheless, there is a complex relationship between autophagy and tumor treatment. Collective studies have documented that autophagy has currently exhibited an essential role for cancer cell survival, hindering the success of the current treatment paradigms. Autophagy inhibition has been accepted as an adjuvant therapy in the context of other therapies, , which has paved the way for the potential combined approach for tumor treatment.…”
Section: Introductionmentioning
confidence: 99%